Media spectacle - Kellner, Douglas, 1943- (Routledge, 2003)
During the mid-1990s, the O.J. Simpson murder trials dominated the media in the United States and were circulated throughout the world via global communications networks. The case became a spectacle of race, gender, class and violence, bringing in elements of domestic melodrama, crime drama and legal drama. According to cultural critic and scholar Douglas Kellner, the Simpson case was just one example of what the author calls 'media spectacle' -- a form of media culture that puts contemporary dreams, nightmares, fantasies and values on display. Through the analysis of several such media spectacles -- including Elvis, the X Files, Michael Jordan, and the Bill Clinton sex scandals - Kellner's insightful and fascinating book draws out important insights into media, journalism, the public sphere and politics in an era of new technologies. Media Spectacle is a brilliant dissection of contemporary society; its ongoing appetite for scandal, tragedy and perversion; and the new technologies and media that strive to feed this immense hunger. This is cultural criticism and media analysis at its best.